2017
DOI: 10.3389/fmicb.2017.01613
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Commensal Bacteria Corynebacterium pseudodiphtheriticum Improves Resistance of Infant Mice to Respiratory Syncytial Virus and Streptococcus pneumoniae Superinfection

Abstract: Corynebacterium pseudodiphtheriticum is a Gram-positive bacterium found as a member of the normal microbiota of the upper respiratory tract. It was suggested that C. pseudodiphtheriticum may be potentially used as a next-generation probiotic for nasal application, although no deep studies were performed in this regard. We hypothesized that human isolate C. pseudodiphtheriticum strain 090104 is able to modulate the respiratory innate immune response and beneficially influence the resistance to viral and bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
122
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(132 citation statements)
references
References 40 publications
6
122
1
3
Order By: Relevance
“…In addition, viable Corynebacterium pseudodiphtheriticum significantly reduced S. pneumoniae cell counts in lungs and prevented its dissemination into the blood stream 101 . A similar protective effect against RSV‐pneumococcal superinfection, mediated by TLR‐3 activation, was observed in infant mice with the intranasal administration of viable, but also nonviable Lactobacillus rhamnosus or its purified peptidoglycan 101 . In addition, treatment of mice with anti‐IFN‐γ or anti‐IL‐10 monoclonal antibodies diminished their capacity to reduce lung bacterial cell counts and lung tissue injuries 102 .…”
Section: Airway Microbiomementioning
confidence: 98%
See 2 more Smart Citations
“…In addition, viable Corynebacterium pseudodiphtheriticum significantly reduced S. pneumoniae cell counts in lungs and prevented its dissemination into the blood stream 101 . A similar protective effect against RSV‐pneumococcal superinfection, mediated by TLR‐3 activation, was observed in infant mice with the intranasal administration of viable, but also nonviable Lactobacillus rhamnosus or its purified peptidoglycan 101 . In addition, treatment of mice with anti‐IFN‐γ or anti‐IL‐10 monoclonal antibodies diminished their capacity to reduce lung bacterial cell counts and lung tissue injuries 102 .…”
Section: Airway Microbiomementioning
confidence: 98%
“…Conversely, changes in microbial community composition constitute a heightened element of risk towards viral respiratory infections and bacterial superinfections (Figure 4). 101,102 …”
Section: Airway Microbiomementioning
confidence: 99%
See 1 more Smart Citation
“…35,36 Furthermore, nasal application of Coryne bacterium spp induced resistance against respiratory syncytial virus and secondary pneumococcal pneumonia in infant mice. 37 These findings emphasise the need for future research efforts to assess the combined effects of these commensal bacteria in modulation of the respiratory ecosystem, especially the containment of potential pathogens such as respiratory syncytial virus, Haemophilus spp, and Streptococcus spp, and of host immune responses underlying respiratory symptoms.…”
Section: (N=108) D (N=171) E (N=100) F (N=78)mentioning
confidence: 98%
“…Another study suggested that this was due to a priming effect, showing that nonviable L. rhamnosus or the bacterial cell wall component peptidoglycan can enhance inflammatory responses in a TLR3-dependent manner (240). In a similar manner, TLR3-dependent priming with the upper respiratory tract-resident species Corynebacterium pseudodiphtheriticum also improved the outcome of RSV and secondary S. pneumoniae infection (241). While these studies emphasized the effect of priming on pulmonary resistance to subsequent infection, it is plausible that these microbiota also influence host tolerance mechanisms.…”
Section: Lung Microbiome In Host Tolerancementioning
confidence: 98%